Persistent ST Segment Elevation After Repeated Percutaneous Coronary Intervention: A Dressler Syndrome? - Eka Ginanjar; Tanya Herdita (Acta Medica Indonesiana, 2023)
In the era of percutaneous coronary intervention (PCI), Dressler syndrome has become an extremely rare phenomenon. Originally known as post-myocardial infarction syndrome, it is characterized by fever, pleuritic chest pain, and pericardial or pleural effusion after myocardial infarction. It is one of the sub-entities of post-myocardial infarction pericarditis (PMIP). A 62-year-old man presented with persistent chest pain and diffuse ST segment elevation even after repeated PCIs. This condition was accompanied by fever and bilateral pleural effusion upon chest X-ray. The patient showed improvement in ST segment elevation and clinical condition after 2 weeks of steroid administration. The findings in this case suggest the possibility of PMIP. Although uncommon, physicians should be aware of the potentials of this condition in the differential diagnosis of chest pain after myocardial infarction and PCI so that immediate effective treatment can be given.